Measuring Social Capital: An Adaptation and Translation into Arabic of the Onyx and Bullen Social Capital Scale for Iraqi-Canadians. Issue 4 (2nd October 2018) - Abdulahad, Raika; Brownlee, Keith; Graham, John R.; Montelpare, William J.
ABSTRACT: Social capital has gained increasing attention from social workers as a way to understand the social networks and resources available to clients, especially new immigrants. Although researchers have developed helpful measures of social capital, a need remains to translate these tools into the native languages of immigrants, while addressing any specific cultural considerations. It would be beneficial for social workers to have access to an Arabic version of a social capital scale. This article describes the process of translation and cultural adaptation of the Onyx and Bullen social capital scale from English to Arabic. Using the responses from 326 Iraqi-Canadians, the instrument was factor analysed to verify the underlying conceptual structure. The translated instrument was found to be consistent with Onyx and Bullen's original factorial structure and to have good internal reliability with a Cronbach coefficient alpha for the overall instrument, which was comparable to the original scale. IMPLICATIONS Social workers' roles in Australia and Canada need to enhance culturally competent social and mental health services to immigrants and refugees. Schools of Social Work in Australia and Canada can increase the preparation of students to work with immigrants and refugees, which can potentially help in energising the economy. Social workers could use this scale to assess the level of social support and integration of Arabic speaking individuals, especially newcomers to Australia and Canada.